Attitude and readiness of gifted and talented students on differentiated instruction in Malay language teaching and learning - Mior Muhammad Saiful Nizan Mohd Saali, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2019)
This study aims to examine the attitude and readiness of gifted and talented students towards teaching and learning in learning in Malay language subjects. A total of 60 students in Pusat PERMATApintar Negara Universiti Kebangsaan Malaysia in this survey study. The data were analyzed descriptively using frequency, means, percentage and standard deviation. The analysis found that the attitude and the readiness of the students were at high levels. Inferential analysis using t-test and correlation found that there was a significant readiness differences between male and female students towards differentiated instruction in the teaching and learning of Malay language. While there was no significant difference between male and female towards differentiated instruction approach in the teaching and learning of Malay language. From the analysis, differentiated instruction approach was accepted at the Pusat PERMATApintar UKM and students showed a tendency to study an advanced Malay language. Therefore, the instructors are expected to create a more conducive learning environment and appropriate differentiated instruction strategies in order to enhance students’ interest in learning Malay language.